2003
DOI: 10.1073/pnas.1432391100
|View full text |Cite
|
Sign up to set email alerts
|

Functional reconstitution of COPI coat assembly and disassembly using chemically defined components

Abstract: Coat protein I (COPI)-coated transport vesicles mediate protein and lipid transport in the early secretory pathway. The basic machinery required for the formation of these transport intermediates has been elucidated based on the reconstitution of COPI-coated vesicle formation from chemically defined liposomes. In this experimental system, the coat components coatomer and GTP-bound ADPribosylation factor (ARF), as well as p23 as a membrane-bound receptor for COPI coat proteins, were shown to be both necessary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 45 publications
4
69
1
1
Order By: Relevance
“…While our results contrast with previously reported results 18,28,29,34,35,39,58 in which it was reported that Arf1 and coatomer were sufficient for vesicle formation, they do not necessarily contradict these studies. The population of LUVs generated by the extrusion method, which is a frequently used method that we used in this work, contains many vesicles with diameters between 30 and 150 nm.…”
Section: Discussioncontrasting
confidence: 99%
“…While our results contrast with previously reported results 18,28,29,34,35,39,58 in which it was reported that Arf1 and coatomer were sufficient for vesicle formation, they do not necessarily contradict these studies. The population of LUVs generated by the extrusion method, which is a frequently used method that we used in this work, contains many vesicles with diameters between 30 and 150 nm.…”
Section: Discussioncontrasting
confidence: 99%
“…Cryo electron microscopy and tomography of liposomes incubated with Arf wt, GTP and coatomer revealed production of regular free COPI vesicles, as expected from earlier work (Reinhard et al 2003). With the nondimerizing mutant of Arf, however, hardly any free vesicles are formed.…”
Section: Budding and Scissionsupporting
confidence: 83%
“…This connection may guarantee incorporation of a v-SNARE into nascent vesicles in order to make them fusion-competent at the appropriate acceptor compartment. The classical view for Arf-GAP function has been that GAP-mediated hydrolysis of GTP on Arf1 leads to vesicle uncoating to allow for subsequent fusion (Tanigawa et al, 1993;Bigay et al, 2003;Reinhard et al, 2003). Yet, other studies support the idea that Arf-GAP activity is required for the packaging of cargo into COPI vesicles (Nickel et al, 1998;Pepperkok et al, 2000;Lanoix et al, 2001;Rein et al, 2002;Lee et al, 2004) and for COPI vesicle biogenesis (Yang et al, 2002;Lee et al, 2004).…”
Section: Gcs1 and Endosome-golgi Recyclingmentioning
confidence: 99%